Do Fund Managers Misestimate Climatic Disaster Risk. (14th February 2020) - Alok, Shashwat; Kumar, Nitin; Wermers, Russ
Abstract: We examine whether professional money managers overreact to large climatic disasters. We find that managers within a major disaster region underweight disaster zone stocks to a much greater degree than distant managers and that this aversion to disaster zone stocks is related to a salience bias that decreases over time and distance from the disaster, rather than to superior information possessed by close managers. This overreaction can be costly to fund investors for some especially salient disasters like hurricanes and tornadoes: a long-short strategy that exploits the overreaction generates a significant DGTW-adjusted return over the following 2 years.